Enhancing Patient Outcomes through Improved Medical Services: A Systematic Review of Evidence-Based Interventions - Elqaroos, Nafisah Abdullah; Aldossary, Sarah Othman; Alajaj, Narjes Salman; AL Qatary, Fatimah Ahmed; Muhanna, Ezdehar Hassan; Alsharif, Rehab Mahmmud; AlSaeedi, Najeeba Baqer; Ali, Rufiah Saad; AL Matrood, Tahera Saeed; Albagal , Roqya Jafar (Journal of Ecohumanism, 2024)
This systematic review aims to evaluate the impact of improved medical services on patient outcomes by analyzing evidence-based interventions. By reviewing studies from databases such as PubMed and the Cochrane Library and applying strict inclusion and exclusion criteria, this review synthesizes data from a range of clinical settings and patient populations. The findings reveal significant correlations between specific medical service enhancements and improved patient health outcomes, providing valuable insights for healthcare professionals and policymakers aiming to optimize care quality and effectiveness. The review underscores the need for ongoing improvement in healthcare practices to ensure sustained patient benefits.